Modelling of layered cylindrical dielectric resonators with reference to whispering gallery mode resonators - Cherenack, K. H. (Kunigunde Hadelinde) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--University of Stellenbosch, 2002.